DEVELOPING DIGITAL TEACHING MATERIALS FOR ELEMENTARY ENGLISH LEARNING: DESIGN, FEASIBILITY, AND EFFECTIVENESS - Munawar Munawar; Kristina Gita Permatasari (Sensei International Journal of Education and Linguistic, 2024)
English learning in elementary school needs interesting teaching materials because the students are still young learners. However, in many schools the teachers still use printed books only, so the students easily get bored. This study discusses the development of digital teaching materials for English learning in elementary school. The study used research and development with the ADDIE model. The data were collected through interviews, questionnaires, expert validation, and a learning test. The result shows that the digital teaching materials are valid, practical, and effective, and the students are more enthusiastic when they use the materials. So, it can be concluded that digital teaching materials are good to be used in elementary English learning.